Primeros datos sobre el ciclo de la materia orgánica en tres bosques caducifolios del Moncayo (Zaragoza) - Carceller F.; Santacecilia M.A.; Vallejo V.R. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Three plots have been selected in different forest ecosystems in the Moncayo Natural Park (Zaragoza): two deciduous oak forests (Quercus petraea and Quercus pyrenaica) located at an altitude of 1050 m, and a beech forest at 1300 m. Litter production has been collected during the period October-86 to September-87; the total annual production of litter was 4.25 t/ha for beech (leaves contributed about 78 per cent), 3.60 t/ha for Q. petraea (87 per cent leaves) and 4.90 for Q. pyrenaica (87 per cent leaves). Litter bags studies allowed the determination of litter decomposition rates. The loss of dry matter was 13 per cent for beech, 25 per cent for Q. petraea and 33 per cent for Q. pyrenaica, after a year of incubation. The decomposition had two maxima (autumn and winter). Differences in decomposition are supposed to be related to the different climatic conditions in the three forest sites.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)